The incidence of senile cataract and glaucoma is increased in patients with plasma cell dyscrasias: etiologic implications - Hemminki, Kari; Försti, Asta; Goldschmidt, Hartmut (Scientific reports, 2016)
Plasma cell dyscrasias, including monoclonal gammopathy of undetermined significance (MGUS), multiple myeloma (MM), Waldenström macroglobulinemia (WM) and light chain AL amyloidosis, are characterized by clonal expansion of plasma cells which produce a vast amount of an immunoglobulin-derived M-protein. We noted that MGUS diagnosis often coincided with diagnoses of senile cataract and glaucoma and tested the associations of MGUS, MM, WM and AL amyloidosis with subsequent eye diseases identified from the Swedish patient registers between 1997 and 2012. Standardized incidence ratios (SIRs) for senile cataract was significantly increased to 1.80 after MGUS, 1.70 after MM, 1.85 after WM and 2.31 after AL amyloidosis. The SIR for glaucoma was 1.60 after MGUS, 1.76 after WM and 2.18 after AL amyloidosis. All SIRs decreased systematically from age below 60 years to over 79 years, but most risks were also significant in age group over 79 years. The M-protein and the related increase in blood viscosity could be a novel etiologic discovery for these common eye diseases. As MGUS prevalence is around 3% at 60 years and close to 10% at age over 80 years, its contribution to the eye disease burden is expected to be remarkably high.